STEAM Approach Learning to Build Complete Knowledge in Fiqih Lesson Themes Halal and Haram Food - Rochmat, Cecep Sobar; Darda, Abu; Huwaida, Jaziela; Maulaya, Rosendah Dwi; Hidayatin, Eka; Setiamawati, Putri (JURNAL PENDIDIKAN SAINS (JPS), 2024)
The complexity of technology has changed the paradigm of society that tends to be happy with instant things. This also happens in the process of food processing and service. Education about halal and haram food is important in the era of technology and current food trends that are starting to bias halal and haram. STEAM learning can help students understand the concept to face the challenges of the 21st century, especially studying the concept of halal and haram food. The purpose of this study is to describe how STEAM-based learning can build complete knowledge related to halal and haram food. This research is a type of critical literature study research with the Cresswell analysis knife. Data sources are taken from the Scopus database, web science of direct and Google Scholar. The findings obtained are that the STEAM approach, including science, can be used to analyze food substances so that students know how halal food is from a scientific perspective. Learning using technology makes students understand food processing. Meanwhile, learning food engineering will provide a new perspective for students. So, knowing halal and haram food engineering. Likewise, discussing food from its aesthetic elements is also important. Where in Islam there are also rules for eating clean and non-disgusting food. Finally, mathematical literacy is needed for arrange food so that you don't overdo it consuming food. Therefore, the integration of halal and haram food learning with the STEAM approach can teach students more complete knowledge of halal and haram food using 21st century competencies.